Effect of different limb lengths on quality of life, eating patterns and gastrointestinal symptoms after Roux‐en‐Y gastric bypass in superobese patients: randomized study - Nergård, B. J. (BJS Open, 2020)
BACKGROUND: Distal Roux‐en‐Y gastrojejunal bypass (DRYGJB) gives better weight reduction than standard Roux‐en‐Y gastric bypass (RYGB) but at the risk of increased malnutrition side‐effects. This study compared the effects of RYGB and DRYGJB on gastrointestinal symptoms, eating patterns and health‐related quality of life (QoL). METHODS: This was a single‐blind RCT from a university‐affiliated obesity centre. Patients with a BMI of 50 kg/m(2) or above were invited to participate. Treatment arms were standard gastric bypass with an alimentary limb of 150 cm and a biliopancreatic limb of 60 cm, with a variable common channel length, or DRYGJB with biliopancreatic limb of 200 cm, common channel limb of 150 cm and variable alimentary limb length. Baseline and follow‐up data to 5 years on quality of life, obesity‐related problems and gastrointestinal symptoms were collected using prospectively created and validated questionnaires. RESULTS: Some 140 patients were included. Those with a DRYGJB had better weight loss at 5 years (mean(s.d.) 68·3(21·8) kg versus 55·7(19·8) kg for standard RYGB; P = 0·011). Eating patterns improved, with no difference between the groups. Gastrointestinal symptoms (diarrhoea, indigestion) worsened significantly in both groups, but only patients with DRYGJB had significantly worse diarrhoea at the end of the study than at baseline (P = 0·006). Both groups had improved perceived generic QoL over baseline, and obesity‐related problems were markedly reduced. CONCLUSION: Standard RYGB and both improved generic and disease‐specific QoL and eating behavioural pattern. Diarrhoea was increased more following DRYGJB than after RYGB. Registration number: NCT 01514799 (https://clinicaltrials.gov).